Method for coating nitramine explosive particles with energetic polymer nitrocellulose and nitramine explosive particles
By coating with nitrocellulose on the surface of nitroamine explosives, the problem of insufficient interaction between nitroamine explosives and propellant matrix is solved, and the mechanical properties of propellant are improved and the energy properties of propellants are maintained.
Patent Information
- Application Number
- CN202411920284.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-04
AI Technical Summary
Due to the lack of stable interaction between the existing nitroamine explosives in the propellant, the interface is weak, and it is prone to "debonding" and "dehumidification" phenomena, which damages the mechanical properties of the propellant, especially under low temperature conditions.
The energy-containing polymer nitrocellulose is used as the coating material, and a uniform and dense coating layer is formed on the surface of the nitroamine explosive by solvent replacement method to improve the reactivity and affinity of the explosive and the propellant matrix.
It effectively inhibits the occurrence of 'dehumidification' phenomenon, improves the compatibility of nitramine explosives with propellant matrix, maintains the high energy properties of propellant, simplifies the production process, and reduces costs.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for coating the surface of nitramine explosives, and more specifically, to a method for coating nitramine explosive particles with energetic polymer nitrocellulose, belonging to the technical field of polymer materials. Background Art
[0002] Solid propellant is the main power source for missile weapon launch and propulsion, and it performs work externally by burning. At present, in order to further improve the energy performance of propellants, meet the urgent needs of weapon equipment renewal, and improve the comprehensive performance of weapons, domestic and foreign researchers usually use high-enthalpy and high-density nitramine explosives (such as RDX, HMX, CL-20) as solid fillers in propellants. However, due to the lack of stable interaction between the crystals of such solid fillers and the polymer matrix of the propellant, a weak stress zone is formed between the interface of the two, which makes the filler easy to fall off under the action of external force, resulting in pores, "debonding" and "dehumidification", etc., which damages the mechanical properties of the propellant, especially the low-temperature mechanical strength. This will further cause unstable combustion of the propellant, resulting in a sudden increase in pressure and even explosion. One way to solve this problem is to coat the surface of the nitramine explosive with a high modulus elastic material, so as to form a hard and tough interface layer between the explosive and the propellant matrix to prevent the occurrence of "dehumidification".
[0003] Zhang Shijie et al. used in-situ polymerization to generate a uniform and dense layer of urea-formaldehyde resin on HMX and CL-20; Jia Xinlei et al. successfully coated a thick layer of polymethyl methacrylate polymer on the surface of RDX by emulsion polymerization; Wang Xijin et al. combined in-situ polymerization with gel method to achieve double-layer coating of polydopamine and titanium dioxide on the surface of RDX. However, traditional coating materials such as polydopamine and polyurethane are inert substances, and introducing them into propellants will undoubtedly reduce the overall energy level. At the same time, traditional coating methods such as emulsion polymerization and self-polymerization are complicated to operate, making it difficult to achieve industrial-grade production, which limits the actual application effect.
[0004] Nitrocellulose (NC) is produced by the exothermic esterification reaction of cellulose and nitric acid. It has excellent film-forming properties and mechanical properties and is widely used in coatings, adhesives and other fields. In addition, NC is also an important mechanical skeleton and energetic component in double-base propellants, with good energy performance, combustion performance and complete combustion. Therefore, by using NC as the coating layer of ammonium nitrate explosives and adjusting the NC content, the energy, oxygen balance and gas generation rate of the coating layer can be effectively controlled; at the same time, nitrocellulose can react with the curing agent in the composite solid propellant, thereby forming a stable bond with the adhesive in the propellant to prevent the occurrence of "dehumidification". Wang Yi et al. prepared HMX / NC nanocomposites using an improved sol-gel-supercritical method, but this method is complicated to operate, the product quality consistency is poor, and it is not universal.
[0005] Based on this, the present invention proposes a method for coating nitrocellulose with nitramine explosive particles by a simple solute replacement-evaporation method to solve the problems existing in the field of surface modification of ammonium nitrate explosives. Summary of the invention
[0006] The purpose of the present invention is to solve the above-mentioned deficiencies of the prior art, thereby providing a method for coating nitramine explosive particles with energetic polymer nitrocellulose, which is a purely physical coating, which can not only improve the reactivity and affinity between the nitramine explosive and the propellant matrix, inhibit the occurrence of the "dehumidification" phenomenon, but also maintain the high energy properties of the nitramine explosive. The method is simple to operate, environmentally friendly, low-cost, short in processing time, and has good product effects.
[0007] The technical solution of the present invention is: a method for coating nitramine explosive particles with energetic polymer nitrocellulose, comprising the following steps: Preparation of nitrocellulose solution Accurately weigh nitrocellulose, add it to the mixed solution of ethanol and acetone under continuous magnetic stirring, and continue stirring until the nitrocellulose is completely dissolved to form a uniform solution; Preparation of homogeneous dispersion solution of nitramine explosive Accurately weigh the nitramine explosive, add it to the deionized water, and after continuous magnetic stirring, ultrasonic oscillation to make the nitramine explosive evenly dispersed without agglomeration; Nitramine explosive surface coating The obtained nitrocellulose solution is dripped dropwise into a homogeneous dispersion solution of nitroamine explosive at a certain temperature which is continuously stirred, and stirring is continued after the dripping is completed to form nitrocellulose-coated nitroamine explosive by a solvent replacement method; Clean and dry The nitroamine explosive coated with nitrocellulose was rinsed with deionized water and anhydrous ethanol for several times, and then placed in an oven for drying to drive off the residual solvent on the surface.
[0008] Preparation of nitrocellulose solution, The nitrogen content of nitrocellulose is 11.80-12.00%, the mass is 100-500 mg, the volume of the mixed solution of ethanol and acetone is 25±2 mL, the volume ratio of the two is 1:4-1:1, the magnetic stirring speed is 250-500 r / min, and the stirring time is 30±3 min.
[0009] The type of nitramine explosive is one of RDX, HMX and CL-20, the particle size is 50-100 μm, the mass is 0.5-1.0 g, the deionized water content is 50±5 mL, the magnetic stirring speed is 250-400 r / min, the stirring time is 30±3 min, and the ultrasonic time is 20-40 min.
[0010] Nitrazol surface coating, The coating temperature is 40~60℃, the stirring speed is 250~400 r / min, the titration speed of the nitrocellulose solution is 0.025±0.003 ml / s, and the stirring time after the addition is completed is 10±1min.
[0011] Nitrazol surface coating, The obtained nitrocellulose solution was titrated dropwise using a constant pressure separatory funnel.
[0012] Cleaning and drying, First rinse with deionized water 3 to 5 times, then rinse with anhydrous ethanol 3 to 5 times. The drying temperature of the oven is 45 to 60°C, and the drying time is 24 to 36 hours.
[0013] A nitramine explosive particle coated with energetic polymer nitrocellulose prepared by the method described in the above scheme.
[0014] An application of nitramine explosive particles coated with energetic polymer nitrocellulose as described in the above scheme in solid propellants.
[0015] The present invention firstly adopts nitrocellulose as a coating material, dissolves it in a mixed solvent of ethanol and acetone, then adds it dropwise into a deionized water phase dispersed with nitramine explosive, realizes the precipitation and attachment of nitrocellulose on the surface of nitramine explosive by means of a solvent replacement method, and further realizes the surface coating of nitramine explosive under the action of heating. The whole reaction process is carried out in the water phase, the coating efficiency is high, and it can be used for nitramine explosives of different sizes, shapes and types, and has good universality.
[0016] The present application provides a method for coating nitramine explosive particles with energetic polymer nitrocellulose. Compared with the prior art: (1) The present invention realizes the preparation of coated nitramine explosives by means of a solvent replacement method. The entire reaction process is carried out in an aqueous phase, which is environmentally friendly, low in cost, and high in coating efficiency. It can be used for nitramine explosives of different sizes, shapes, and types. (2) The coating material for nitramine explosives used in the present invention is nitrocellulose, which has good energy performance, combustion performance and combustion completeness. It can improve the interfacial compatibility between nitramine explosives and propellant matrix while maintaining a high overall energy level of the propellant, thereby solving the problem of serious propellant specific impulse reduction caused by traditional inert coating materials. DETAILED DESCRIPTION
[0017] The technical solution provided by the present invention is described in detail below in conjunction with embodiments. It should be understood that the following specific implementation methods are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0018] In a first aspect, the present invention provides a method for coating nitramine explosive particles with energetic polymer nitrocellulose, comprising: Step 1: Preparation of nitrocellulose solution: accurately weigh a certain mass of nitrocellulose, add it into a mixed solution of ethanol and acetone under continuous magnetic stirring, and continue stirring for a certain period of time to completely dissolve the nitrocellulose and form a uniform solution; Step 2: Preparation of a homogeneous dispersion of nitramine explosive: accurately weigh a certain mass of nitramine explosive, add it into a beaker containing deionized water, and after continuous magnetic stirring, ultrasonically oscillate for a certain period of time to uniformly disperse the nitramine explosive without agglomeration; Step 3: Surface coating of nitramine explosive: placing the homogeneous dispersion solution of nitramine explosive obtained in the second step on a magnetic stirrer and continuously stirring at a certain temperature; then adding the nitrocellulose solution obtained in the first step into a constant pressure separatory funnel, and adding dropwise to the homogeneous dispersion solution of nitramine explosive, and continuing to stir for a certain period of time after the dropwise addition is completed, to obtain nitrocellulose coated nitramine explosive; Step 4: Cleaning and drying of coated nitramine explosives: The nitrocellulose coated nitramine explosives obtained in the third step are rinsed with deionized water and anhydrous ethanol for several times, and then placed in an oven for drying to drive off residual solvent on the surface.
[0019] Furthermore, the nitrogen content of the nitrocellulose described in the first step is 11.80~12.00%, the mass is 100-500 mg, the volume of the mixed solution of ethanol and acetone is 25±2 mL, the volume ratio of the two is 1:4~1:1, the magnetic stirring speed is 250~500 r / min, and the stirring time is 30±3min.
[0020] Furthermore, the type of nitramine explosive described in the second step is one of RDX, HMX and CL-20, the particle size is 50-100 μm, the mass is 1~1.0 g, the deionized water content is 50±5 mL, the magnetic stirring speed is 250~400r / min, the stirring time is 30±3 min, and the ultrasonic time is 20~40 min.
[0021] Furthermore, the reaction temperature in the third step is 40-60°C, the stirring speed is 250-400 r / min, the titration speed of the separatory funnel is 0.025 ± 0.003 ml / s, and the subsequent continuous stirring time is 10 ± 1 min.
[0022] Furthermore, the deionized water and anhydrous ethanol cleaning times in the fourth step are 3 to 5 times respectively, the drying temperature of the oven is 45 to 60° C., and the drying time is 24 to 36 hours.
[0023] Example 1: 1 g of RDX particles (particle size 50 μm) were coated with 5 mg / mL nitrocellulose solution.
[0024] (1) Accurately weigh 125 mg of nitrocellulose with a nitrogen content of 12% and add it to a mixed solution of 25 mL of ethanol and acetone (volume ratio of 1:1) under continuous magnetic stirring at 250 r / min. Continue stirring for 30 min to form a homogeneous solution. (2) Accurately weigh 1 g of RDX particles (particle size 50 μm) and add them to a beaker containing 50 mL of deionized water. After magnetic stirring at 250 r / min for 30 min, ultrasonic oscillation was performed for 20 min to uniformly disperse the nitramine explosive without agglomeration. (3) The homogeneous dispersion solution of nitramine explosive obtained in the second step is placed on a magnetic stirrer and continuously stirred at 50°C; then the nitrocellulose solution obtained in the first step is added to a constant pressure separatory funnel and added to the homogeneous dispersion solution of nitramine explosive continuously stirred at 50°C at a rate of 0.025 ml / s, and then continuously stirred for 10 min to form nitrocellulose-coated nitramine explosive; (4) The nitrocellulose-coated nitramine explosive obtained in the third step was rinsed with deionized water and anhydrous ethanol three times each, and then placed in an oven at 60°C for 24 h to drive off the residual solvent on the surface.
[0025] (5) The mass of the final nitrocellulose coating layer accounts for 1% of the total mass, and the coating layer is uniform and dense.
[0026] Example 2: 1 g of RDX particles (particle size 50 μm) were coated with a 10 mg / mL nitrocellulose solution.
[0027] (1) Accurately weigh 250 mg of nitrocellulose with a nitrogen content of 12% and add it to a mixed solution of 25 mL of ethanol and acetone (volume ratio of 1:4) under continuous magnetic stirring at 350 r / min. Continue stirring for 33 min to form a homogeneous solution. (2) Accurately weigh 1 g of RDX particles (particle size 100 μm) and add them to a beaker containing 50 mL of deionized water. After magnetic stirring at 350 r / min for 33 min, ultrasonic oscillation was performed for 40 min to uniformly disperse the nitramine explosive without agglomeration. (3) The homogeneous dispersion solution of nitramine explosive obtained in the second step is placed on a magnetic stirrer and continuously stirred at 40°C; then the nitrocellulose solution obtained in the first step is added to a constant pressure separatory funnel and added to the homogeneous dispersion solution of nitramine explosive continuously stirred at 40°C at a rate of 0.028 ml / s, and then continuously stirred for 9 minutes to form nitrocellulose-coated nitramine explosive; (4) The nitrocellulose-coated nitramine explosive obtained in the third step was rinsed twice with deionized water and twice with anhydrous ethanol, and then placed in an oven at 55 °C for 30 h to drive off the residual solvent on the surface.
[0028] (5) The mass of the final nitrocellulose coating layer accounts for 5% of the total mass, and the coating layer is uniform and dense.
[0029] Example 3: 1 g of RDX particles (particle size 50 μm) were coated with 20 mg / mL nitrocellulose solution.
[0030] (1) Accurately weigh 500 mg of nitrocellulose with a nitrogen content of 12% and add it to a mixed solution of 25 mL of ethanol and acetone (volume ratio of 1:2) under continuous magnetic stirring at 500 r / min. Stir for 27 min to form a homogeneous solution. (2) Accurately weigh 1 g of RDX particles (particle size 80 μm) and add them to a beaker containing 50 mL of deionized water. After magnetic stirring at 400 r / min for 27 min, ultrasonic oscillation was performed for 30 min to uniformly disperse the nitramine explosive without agglomeration. (3) The homogeneous dispersion solution of nitramine explosive obtained in the second step is placed on a magnetic stirrer and continuously stirred at 60°C; then the nitrocellulose solution obtained in the first step is added to a constant pressure separatory funnel and added to the homogeneous dispersion solution of nitramine explosive continuously stirred at 60°C at a rate of 0.022 ml / s, and then continuously stirred for 11 min to form nitrocellulose-coated nitramine explosive; (4) The nitrocellulose-coated nitramine explosive obtained in the third step was rinsed once with deionized water and once with anhydrous ethanol, and then placed in an oven at 50 °C for 36 h to drive off the residual solvent on the surface.
[0031] (5) The mass of the final nitrocellulose coating layer accounts for 8% of the total mass, and the coating layer is uniform and dense.
[0032] Comparative Example: Preparation of nitrocellulose coated with RDX by sol-gel method RDX and NC gel are mixed, and then 1,4-butyrolactone is selected as a solvent, HDI is used as a cross-linking agent, and DBTDL is used as a catalyst. The mixture is reacted at 40°C, and cross-linked and cured to prepare a block gel with a good structure. The wet gel is aged at room temperature for 3 days, and then freeze-dried to obtain a NC / RDX nanocomposite energetic material. Compared with the sol-gel method used in the present invention, the operation of the present invention is simpler, and no toxic or harmful curing agents or catalysts are required. At the same time, the obtained coated explosive particles are distinct, and there will be no large amount of agglomeration in the sol-gel method, which has higher practical value. The coating method proposed in the present invention has significant advantages.
Claims
1. A method for coating nitramine explosive particles with energetic polymer nitrocellulose, characterized in that: The following steps are involved: Preparation of nitrocellulose solution Accurately weigh nitrocellulose, add it to the mixed solution of ethanol and acetone under continuous magnetic stirring, and continue stirring until the nitrocellulose is completely dissolved to form a uniform solution; Preparation of homogeneous dispersion solution of nitramine explosive Accurately weigh the nitramine explosive, add it to the deionized water, and after continuous magnetic stirring, ultrasonic oscillation to make the nitramine explosive evenly dispersed without agglomeration; Nitramine explosive surface coating The obtained nitrocellulose solution is dripped dropwise into a homogeneous dispersion solution of nitroamine explosive at a certain temperature which is continuously stirred, and stirring is continued after the dripping is completed to form nitrocellulose-coated nitroamine explosive by a solvent replacement method; Clean and dry The nitroamine explosive coated with nitrocellulose was rinsed with deionized water and anhydrous ethanol for several times, and then placed in an oven for drying to drive off the residual solvent on the surface.
2. A method for coating nitramine explosive particles with energetic polymer nitrocellulose according to claim 1, characterized in that: Preparation of nitrocellulose solution, The nitrogen content of nitrocellulose is 11.80-12.00%, the mass is 100-500 mg, the volume of the mixed solution of ethanol and acetone is 25±2 mL, the volume ratio of the two is 1:4-1:1, the magnetic stirring speed is 250-500 r / min, and the stirring time is 30±3 min.
3. The method of coating nitramine explosive particles with energetic polymer nitrocellulose according to claim 1, characterized in that: The type of nitramine explosive is one of RDX, HMX and CL-20, the particle size is 50-100 μm, the mass is 0.5-1.0 g, the deionized water content is 50±5 mL, the magnetic stirring speed is 250-400 r / min, the stirring time is 30±3 min, and the ultrasonic time is 20-40 min.
4. The method of coating nitramine explosive particles with energetic polymer nitrocellulose according to claim 1, characterized in that: Nitrazol surface coating, The coating temperature is 40~60℃, the stirring speed is 250~400 r / min, the titration speed of the nitrocellulose solution is 0.025±0.003 ml / s, and the stirring time after the addition is completed is 10±1min.
5. A method for coating nitramine explosive particles with energetic polymer nitrocellulose according to claim 1 or 4, characterized in that: Nitrazol surface coating, The obtained nitrocellulose solution was titrated dropwise using a constant pressure separatory funnel.
6. The method of coating nitramine explosive particles with energetic polymer nitrocellulose according to claim 1, characterized in that: Cleaning and drying, First rinse with deionized water 3 to 5 times, then rinse with anhydrous ethanol 3 to 5 times. The drying temperature of the oven is 45 to 60°C, and the drying time is 24 to 36 hours.
7. Nitrazol explosive particles coated with energetic polymer nitrocellulose prepared by the method according to any one of claims 1 to 6.
8. Use of the nitramine explosive particles coated with energetic polymer nitrocellulose as claimed in claim 7 in solid propellants.